Introduction to TOEFL in Improving Kampus Nommensen High School Students' Listening Skills as an Effort to Face Academic and Global Challenges - Simanjuntak, Naomi; Samosir, Tiondina; Sihotang, Tiodor; Saragih, Nova Evelin; Herman, Herman (Universitas Ibn Khaldun, 2025)
This community service aims to improve the listening skills of students at SMA Kampus Nommensen Pematangsiantar through the introduction of the TOEFL test. The program responds to the increasing need for English proficiency in academic and global contexts. The activity involved 20 students from Grade XI and was conducted in three phases: preparation, implementation, and evaluation. During the implementation, a lecture and discussion format was used to deliver material covering the definition, types, benefits, and strategies related to TOEFL. Students were also introduced to practice resources and test venues. The results show that students gained new insights into TOEFL, actively participated in the sessions, and became more aware of the importance of English proficiency for their future. Several challenges were encountered, including limited initial knowledge about TOEFL and lack of motivation. These were addressed through interactive discussions and collaborative support from teachers. This initiative proves to be a valuable step in preparing students to face academic requirements and international opportunities.